(untitled) (Research, Society and Development, 2021)
Treatment of the root canal system (SCR) requires mechanical and chemical techniques to shape, clean and fill the pulp cavity. There are irrigation techniques that enhance the action of irrigants and allow greater access to undesirable substances in the complex system of root canals that are not reached mechanically during the biomechanics of endodontic treatment, thus improving the cleaning and disinfection of the pulp cavity during endodontic therapy and reducing the bacterial load. The aim of the present study was to investigate the method of passive ultrasonic irrigation (PUI) as a technique for circulating irrigation solutions in root canals, its advantages and limitations compared to conventional irrigation methods. To perform this work, a search was conducted in the BVS, SCIELO, PUBMED databases for the last 16 years. 54 relevant articles were considered, from which 15 articles were selected. It is concluded that the ultrasonic technique is widely used because it enhances and directs the irrigation solution along the entire length of the root canal system and its recesses, but its effect may be limited in the apical part of the root due to the morphology of the root canal.